SINERGI TANPA HENTI: STRATEGI COLLABORATIVE GOVERNANCE DALAM MEWUJUDKAN DESA CINGCIN BERSINAR (BERSIH NARKOBA) - Kurniawati Kurniawati; Ginanjar Wira Saputra (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study aims to analyze the implementation of the Collaborative Governance model in efforts to combat the dangers of drugs in Cingcin Village, Bandung Regency. The background of the problem is based on the alarming prevalence of drug abuse in the community and requires multi-sectoral involvement. The method used is descriptive qualitative with data collection through in-depth interviews, participant observation, and documentation studies. The results show that collaborative governance has been formed through a Community-Based Intervention (IBM) forum involving the Village Government, Bhabinkamtibmas, BNN, and community leaders. The novelty of this study reveals that although the pillars of collaboration are active and supported by the village budget, the level of community participation has only reached the partnership stage and is still low among vulnerable youth groups. In conclusion, this model lays a promising foundation for collaboration, but public inclusivity and participation in the planning and evaluation stages need to be improved for program effectiveness.